1990
DOI: 10.1099/00221287-136-7-1343
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of a tetracycline resistance element from Clostridium difficile and its conjugal transfer to and from Bacillus subtilis

Abstract: A tetracycline resistance (Tc') determinant from Closfridium &Bile strain 630 was cloned into the Escherichia coli plasmid vector pUC13. The resulting plasmid pPPM20, containing an insert of 3.4 kbp, was mapped and a 1.1 kbp SucI-Hind111 fragment wholly within the Tcr gene was identified. Dot-blot hybridization studies with the 1.1 kbp fragment showed that the Tcr gene belonged to hybridization class M. Tcr could be transferred between C. &mile strains and to Bacillus subtilis at a frequency of lo-' per donor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
69
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 22 publications
4
69
0
Order By: Relevance
“…One recent study found all isolates of swine origin to be sensitive to metronidazole and vancomycin, 98% were sensitive to chloramphenicol, and 90% were sensitive to tetracycline (20). Previous studies have reported that the majority of C. difficile strains with tetracycline resistance have the tetM gene, which is carried on a conjugative transposon (19). The tetW gene has the second largest host range of the tetracycline resistance genes, second only to tetM.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study found all isolates of swine origin to be sensitive to metronidazole and vancomycin, 98% were sensitive to chloramphenicol, and 90% were sensitive to tetracycline (20). Previous studies have reported that the majority of C. difficile strains with tetracycline resistance have the tetM gene, which is carried on a conjugative transposon (19). The tetW gene has the second largest host range of the tetracycline resistance genes, second only to tetM.…”
Section: Discussionmentioning
confidence: 99%
“…The tet(M) gene is common among enterococci and streptococci, where it is part of broad-host-range conjugative transposons and is thus usually associated with int-Tn, the gene encoding the integrase of these elements (23,24). In contrast, tet(O) is rarely encountered in these genera, where it is carried by conjugative plasmids (33,35,37) (19). Lack of association of tet(M) with int-Tn could be due to deletions in conjugative transposons or to the existence of genetic support(s) other than Tn916-related elements for this resistance determinant in gram-positive cocci.…”
Section: Methodsmentioning
confidence: 99%
“…(29,31). Originally discovered in Streptococcus agalactiae (4), tet(M) has been subsequently detected in a large variety of aerobic and anaerobic gram-positive and gram-negative bacterial genera, including Enterococcus (2, 27, 37), Streptococcus (27,37), Peptostreptococcus (26,27), Staphylococcus (3), Listeria (9,25), Clostridium (11,19), Neisseria (16), Kingella (16), Gardnerella (27), Haemophilus (26), and Bacteroides (1), and in cell wall-less organisms such as Mycoplasma and Ureaplasma spp. (26).…”
mentioning
confidence: 99%
“…Towards this end we have investigated the behaviour of the tetracycline-resistance-encoding conjugative transposon Tn916 and its erythromycin-resistant derivative Tn916˜E (Rubens & Heggen, 1988;Mullany et al, 1991) and the endogenous tetracycline-resistance-encoding conjugative transposon Tn5397 in C. difficile (for a recent review on the properties of these elements see Mullany, 2002, and accompanying articles). All these elements enter the genome of C. difficile CD37 at highly preferred sites (Mullany et al, 1990;Mullany et al, 1991;Wang et al, 2000a). Tn5398 is a transferable genetic element (Mullany et al, 1995); however, it does not contain the genes required for self-conjugation, therefore it is likely to be a mobilizable element (Farrow et al, 2001).…”
Section: Introductionmentioning
confidence: 99%